Redshift evolution of the H2/H i mass ratio in galaxies. Issue 1 (23rd January 2021) - Morselli, Laura; Renzini, A; Enia, A; Rodighiero, G
ABSTRACT: In this paper, we present an attempt to estimate the redshift evolution of the molecular to neutral gas mass ratio within galaxies (at fixed stellar mass). For a sample of five nearby grand design spirals located on the main-sequence (MS) of star-forming galaxies, we exploit maps at 500 pc resolution of stellar mass and star formation rate ( M ⋆ and SFR). For the same cells, we also have estimates of the neutral ( M H i ) and molecular (M_H_2 ) gas masses. To compute the redshift evolution, we exploit two relations: (i) one between the molecular-to-neutral mass ratio and the total gas mass ( M gas ), whose scatter shows a strong dependence with the distance from the spatially resolved MS, and (ii) the one between (M_H_2/M_) and log ( M H i / M ⋆ ). For both methods, we and that M_H_2 / M H i within the optical radius slightly decreases with redshift, contrary to common expectations of galaxies becoming progressively more dominated by molecular hydrogen at high redshifts. We discuss possible implications of this trend on our understanding of the internal working of high-redshift galaxies.